IMF Glossary : English, French, Russian. (International Monetary Fund, 1998)
IMF Glossaries consists of terms, phraseological units, and institutional titles covering areas such as macroeconomics, money and banking, public finance, taxation, balance of payments, statistics, accounting, and economic development. They contain terminology relating to the IMF's organization and operations, as well as from the Articles of Agreement, By-Laws, Rules and Regulations, and other major IMF publications. Since the Glossaries are concept-based, synonyms are consolidated into one single entry. Cross- references refer to the main entry under which the various synonyms are listed ("see") and also draw the user's attention to terms that are related but not synonyms ("see also").